The Effect of Profitability, Leverage, and Capital Intensity on Tax Avoidance (An Empirical Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2019–2023 Period) - Ni Putu Ari Mirayani; Made Yenni Latrini (Digital Innovation : International Journal of Management, 2025)
Tax avoidance is a legal strategy used by companies to minimize their tax burden by exploiting loopholes in tax regulations without violating the law. Although not illegal, this practice may reduce a company’s tax contribution to the state and pose reputational risks. This study aims to analyze the influence of profitability (ROA), leverage (DER), and capital intensity (FAT) on tax avoidance, measured using the Current Effective Tax Rate (CETR), in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research adopts a quantitative approach with multiple linear regression analysis processed using SPSS. The sample was selected using purposive sampling. The results show that all three independent variables have a significant effect on tax avoidance, supported by significance values below the critical threshold and t-values exceeding the t-table, leading to the acceptance of H1, H2, and H3.